2022
DOI: 10.1364/prj.446416
|View full text |Cite
|
Sign up to set email alerts
|

Broadband NIR-emitting Te cluster-doped glass for smart light source towards night-vision and NIR spectroscopy applications

Abstract: Broadband near-infrared (NIR)-emitting materials are crucial components of the next generation of smart NIR light sources based on blue light-emitting diodes (LEDs). Here, we report a Te cluster-doped borate glass, which exhibits ultra-broadband emission around 980 nm with a full-width at half-maximum (FWHM) of 306 nm under blue light excitation. We propose adjustments of glass chemistry and processing condition as a means for topo-chemical tailoring of the NIR photoemission characteristics in such materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Tan et al demonstrated that tellurium cluster‐doped glasses effectively excited by a blue LED can be used as the phosphor for NIR pc‐LEDs. [ 22 ] Their NIR LED showed a promising photoelectric efficiency (≈21.2% at 100 mA), but the precise control of the charge state of tellurium is demanding and poses a great challenge. In comparison, our NIR LED is superior in the compact structure, and offers a large scope for selecting the specific excitation channels at one's request.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al demonstrated that tellurium cluster‐doped glasses effectively excited by a blue LED can be used as the phosphor for NIR pc‐LEDs. [ 22 ] Their NIR LED showed a promising photoelectric efficiency (≈21.2% at 100 mA), but the precise control of the charge state of tellurium is demanding and poses a great challenge. In comparison, our NIR LED is superior in the compact structure, and offers a large scope for selecting the specific excitation channels at one's request.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, NIR phosphors consist of a luminescent ion (dopant) and a host material, such as trivalent (Pr 3+ , Nd 3+ , Er 3+ , Tm 3+ , and Yb 3+ ) [13][14][15][16] or divalent (Eu 2+ ) lanthanide ions (Ln 3+ ), [5,17] transition (Cr 3+ , Cr 4+ , Ni 2+ , Fe 3+ ) [4,[18][19][20][21] or heavy metal (Te, Bi) [12,22] ions doped inorganic crystals and glasses embedded with specially designed nano-or micro-crystals. Currently, the two mostly studied NIR emitting ions of Nd 3+ and Cr 3+ based on intraconfigurational 4f-4f and 3d-3d transitions, respectively, suffer from weak (and narrow-band in case of Nd 3+ ) absorption strength restricted by the Laporte selection rule.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Tan et al achieved NIR luminescence in Tedoped borate glass for the first time by optimizing the content of modifiers in borate glass and introducing C. [118] The composition of glasses are (mol%)49B 27 Al NMR spectra. d-f) Schematic presentation for the modulation of the Te clusters by altering the topological cages.…”
Section: Te-doped Borate Glassesmentioning
confidence: 99%
“…Glasses, together with transparent ceramics, have recently been investigated as practical alternatives to the organic polymer binders for pc-NIR LED devices due to their excellent thermal stability, high durability, and module structure with easy assembly and disassembly. 22,32 Highly transparent glass has no scattering centers and the incident light can travel longer lengths and thus has a higher probability of being absorbed when it encounters NIR active centers; however, the research is still mainly focused on the NIR-I region. Fortunately, we note that Bi within various glass systems can exhibit tunable and broadband luminescence in almost the entire NIR region (800-1800 nm), and shows strong and wide absorption in the UV-Vis and NIR region.…”
Section: Introductionmentioning
confidence: 99%